Can diversity promote trust? Neighbourhood context and trust in the police in Northern Ireland. (22nd November 2019) - Bradford, Ben; Topping, John; Martin, Richard; Jackson, Jonathan
ABSTRACT: The association between trust in the police and neighbourhood context is well known. Police seem to enjoy more trust when community settings are perceived as orderly, cohesive and well-functioning, and trust seems to be lower when order and cohesion seem attenuated or under threat. Yet, little attention has been paid to the association between neighbourhood diversity and trust in the police. Allport's contact hypothesis suggests that because diversity increases intergroup contact and thus a sense of cohesion, it may promote trust in the police. We use data from a nationally representative survey conducted in 2014, combined with Census and other local-area data, to explore the association between ethno-religious diversity and trust in the Police Service of Northern Ireland. We find that trust is higher in more diverse areas, primarily because Catholics living in such areas report significantly higher levels of trust than their counterparts living in less diverse areas. We interpret these results in light of what policing means in contemporary Northern Ireland, almost two-decades after the country's landmark reform of policing began.